Effort Maximization in Asymmetric N-person Contest Games - Jörg Franke; Christian Kanzow; Wolfgang Leininger; Alexandra Väth (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper provides existence and characterization of the optimal contest success function under the condition that the objective of the contest designer is total effort maximization among n heterogeneous players. Heterogeneity of players makes active participation of a player in equilibrium endogenous with respect to the specific contest success function adopted by the contest designer. Hence, the aim of effort maximization implies the identification of those players who should be excluded from making positive efforts.We give a general proof for the existence of an optimal contest success function and provide an algorithm for the determination of the set of actively participating players.This is turn allows to determine optimal efforts in closed form.An important general feature of the solution is that maximization of total effort requires at least three players to be active.
Keywords: C72; D72; 330; Effort maximization; existence of solution; asymmetric contests; participation constraints; Leistungsanreiz; Wettbewerb; Extensives Spiel; Leistungsmotivation; Theorie